Hydrogen production by an enriched photoheterotrophic culture using dark fermentation effluent as substrate: Effect of flushing method, bicarbonate addition, and outdoor–indoor conditions. (10th August 2015) - Montiel-Corona, Virginia; Revah, Sergio; Morales, Marcia
Abstract: This work compares the photo-fermentative hydrogen production by an enriched photoheterotrophic culture (IZT) and by Rhodobacter capsulatus under outdoor or indoor conditions using dark fermentation effluent (DFE) as substrate, and argon, CO2 and reduced pressure for flushing the headspace and bicarbonate as electron sink. The highest H2 production (1478 ± 17 mL H2 L −1 with 89% COD removal) was obtained under indoor conditions by the IZT culture with reduced pressure and 250 mg L −1 of NaHCO3, followed by R. capsulatus (1252 ± 20 mL H2 L −1 with 65% COD removal) under the same conditions. Outdoor H2 production was reduced to 883 ± 4 and 866 ± 46 mL H2 L −1 with IZT culture and R. capsulatus, respectively. Poly-3-hydroxybutyrate accumulation was up to 5% for IZT culture and 29% for R. capsulatus . Enhancement on hydrogen production using reduced pressure and DFE along with the achieved COD removal and poly-3-hydroxybutyrate accumulation can contribute to abate the costs of hydrogen production. Highlights: High hydrogen yields were achieved by the photoheterotrophic IZT culture. Reduced pressure in headspace improves the H2 production with respect to Ar. The IZT consortium showed a high capacity for COD removal. Rhodobacter capsulatus accumulated up to 29% in weight of PHB at outdoor conditions. H2 production at outdoors is attractive considering the potential energy savings.